Multiscale modeling of the anisotropic electrical conductivity of architectured and nanostructured Cu-Nb composite wires and experimental comparison. (December 2017) - Gu, T.; Medy, J.-R.; Volpi, F.; Castelnau, O.; Forest, S.; Hervé-Luanco, E.; Lecouturier, F.; Proudhon, H.; Renault, P.-O.; Thilly, L.
Abstract: Nanostructured and architectured copper niobium composite wires are excellent candidates for the generation of intense pulsed magnetic fields (> 90T) as they combine both high electrical conductivity and high strength. Multi-scaled Cu-Nb wires can be fabricated by accumulative drawing and bundling (a severe plastic deformation technique), leading to a multiscale, architectured and nanostructured microstructure providing a unique set of properties. This work presents a comprehensive multiscale study to predict the anisotropic effective electrical conductivity based on material nanostructure and architecture. Two homogenization methods are applied: a mean-field theory and a full-field approach. The size effect associated with the microstructure refinement is taken into account in the definition of the conductivity of each component in the composites. The multiscale character of the material is then accounted for through an iterative process. Both methods show excellent agreement with each other. The results are further compared, for the first time, with experimental data obtained by the four-point probe technique, and also show excellent agreement. Finally, the qualitative and quantitative understanding provided by these models demonstrates that the microstructure of Cu-Nb wires has a significant effect on the electrical conductivity. Graphical abstract: Image 1